Transpersonal experience as a response to the challenges of nihilism: the European context - A. Y. Morozov; M. M. Rohozha (Ukrainian Cultural Studies, 2021)
The authors of the article focus their attention on the question of spirituality as an existential attitude of a person to the sacred mystery of being. The ambivalence of the realm of the sacred is that being transcendental at the same time in the act of Epiphany it manifests itself in a variety of symbolic forms of personal experience. It is argued that spirituality par excellence is transpersonal experience, which communicates the personality with the secret of the sacred as incomprehensible, not intellectually, but through existential involvement. In this intuitive experience of spiritual inspiration, the inexpressible truth of things beyond "facts" and "texts" is revealed to man. Transpersonal experience is constitutive in the process of a person’s formation, his humanization. The transcendence of the individual takes place in it, which presupposes a constant movement of self-improvement and self-overcoming, expansion of consciousness. This can be called spiritual initiation through a gradual moral transformation of the personality through symbolic death and resurrection, the purpose of which is the realization of existential fullness and the achievement of happiness-bliss. Historical forms of spiritual initiation are analyzed, such as the ancient mysteries and the Christian sacrament of the Eucharist. Particular attention is paid to the analysis of the Platonic understanding of inspiration-madness. It is noted that in the depths of modern secular culture, which is a consequence of the nihilistic attitude towards "disenchanting the world" and moral relativism, nostalgia for the sacred is inevitably born. Heidegger’s teaching states that the roots of modern world disengagement, nihilism, and the oblivion of the sacred truth of being should be sought in the very history of being, that is, in objective "ontohistory". At the same time, it depends on the will of man whether he wants to abandon his nihilistic and cynical utilitarian-pragmatic attitude of worldview, and change the mode of existence to a useless "essential" attitude to reality. Nostalgia for the fullness of life, for a holistic picture of the world, on one hand, and the soulless technocratic and objective nature of modern civilization, dominated by alienation and impersonality, on another hand, should be a turning point on the way to the main event of ontohistory – the revenge of the sacred and the return of the "last god".